Results Readiness in Social Protection and Labor Operations : Technical Guidance Notes for Social Service Delivery Projects - Van Domelen, Julie (World Bank, Washington, DC, 2017)
The social protection (SP) portfolio includes a number of operations that are focused on improving service delivery across a broad range of social services. These service delivery goals are typically oriented to improving access to and quality of social services, usually as part of broader government reform and decentralization strategies. There is one case of this type of a project in an emergency context, ensuring access to basic services as an important complement to a safety net strategy. There are other complementarities between safety nets and service delivery projects, for example many safety net programs like Conditional Cash Transfers (CCTs) rely on the basic functioning of health and education services in the vicinity of program beneficiaries. The cohort includes 12 social service delivery-oriented SP projects representing about 15 percent of the cohort with an average of 2 operations approved per year in the period FY05-09. Despite the relatively lower frequency of this type of SP operation, there was broad regional representation with 5 in AFR, 4 in Latin America and Caribbean (LAC) and one each in Middle East and North Africa (MENA), South Asia Region (SAR) and Europe and Central Asia (ECA). The group is evenly divided between policy-based and investment lending, with six policy-based Development Policy Loan (DPL) and Private Sector Committee (PSC) projects, four specific investment projects, one technical assistance, and one emergency recovery project. The prominence of DPLs underscores the policy type of objectives often found in these projects. The DPLs range from PRSCs and DPLs with broader country focus, like Madagascar and Niger, to DPLs more narrowly focused on social services, as is the case of a series of DPLs in Peru. Investment lending ranges from stabilization of social services in response to crisis in the West Bank and Gaza, to longer-term institutional objectives of decentralizing social service delivery and financing in Serbia and Ethiopia. In terms of institutional objectives, these projects most typically focus on sector institutions and decentralization strategies. There is less of a focus on the community level than on sub-national government roles and responsibilities.